Mechanical modelling and analysis of CMOS image sensor package - Lim, T.S.; Sukiman, Muhamad Shafiq; Jasmee, Solehah; Masdzarif, Nur Diana Izzani (2023)
The growth of automotive industry not only focus on power efficiency and carbon emission reduction, it also has makes further progress in the areas of advanced driver assistance systems (ADAS) and autonomous driving (AD) technologies. With the progressive technology breakthrough and heavily studies in these two areas, the demand for imaging cameras is steadily increasing to support applications such as lane detection, traffic sign detection, pedestrian/vehicle recognition and driver monitoring. Consequently, this drives higher demand for image sensor packages to meet stringent automotive reliability requirements. In the past, high reliability image sensor packages are typically with ceramic based packages, these tend to have considerably higher costs and longer development cycles than laminate-based packages which are normally used in high speed, RF or MEMS market segment. Therefore, it is important to ensure a high reliability for the laminate-based packages by studying the package design. This can be done by finite element analysis (FEA) which is a fast and cost-efficient method in analyzing the stress experienced by the package. This paper discusses the effects of different package designs on the package stress using the FEA simulation method.